Design and fabrication of a new replaceable nozzle for abrasive water jet application - Nuraini, Lusi; Gebremariam, Mebrahitom; Alao, Abdur-Rasheed; Saptaji, Kushendarsyah; Mohd Azmir, Mohd Azhari (Springer, 2025)
Nozzles are critical to the quality of the cuts produced during abrasive waterjet machining. The quality of the results of AWJ machining depends on the focus of the nozzle, which increases over time due to the aggressiveness of the abrasive particles that wear the inner wall of the nozzle. The purpose of this study is to explore fundamentally new terms to increase the wear resistance of the nozzle for the abrasive jet machine and increase its durability. This study mainly dealing with the designing and fabrication of a new replaceable nozzle. Compared to the traditional nozzle, which needs to be replaced regularly, this new replaceable nozzle offers a special feature in terms of recyclability. The new interchangeable parts, manufactured using additive manufacturing, consist of two parts: 50% of the inlet and 50% of the outlet of the entire nozzle length, using a screw thread mechanism. Accelerated wear test conducted to study the wear progression. The result showed that the exit diameter increased by more than 50% compared to the initial diameter and had a linear relationship with time. Weight loss measurement indicate a powerful tool in nozzle wear characterization.